Impression Management in the Communications Services for New Student Admissions at Private Universities in West Java - Tresna Wiwitan; Sophia Novita; Khalifia Rahma Nidya (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Currently, societal interaction patterns, especially those of colleges, affect how people perceive an institution. Institutions must be able to harmonize all internal elements by positioning Private University as a service institution that is able to